Exploring crisis management response to hybrid threats and warfare - Tikanmäki, Ilkka; Ruoslahti, Harri (Journal of military studies, 2024)
Crisis management (CM) operations and organisations may face internal, external and hybrid threats (HTs) against their information and/or personnel. This research looks at how selected European Union (EU), North Atlantic Treaty Organization (NATO) and national perspectives address internal, external and global HTs and influence, even warfare, and maps some relevant strategies to prepare against them in a CM context. Strategies to fight against HTs include relevant political debate and decision-making, integration of EU- and national-level security into critical infrastructure and regular preparedness exercises. Responses to HTs call for relevant technical, situational awareness and problem-solving skills. This research shows how collaboration and situation understanding can assist in detecting and responding to possible cyber and HTs against CM operations. This study examines how collaboration and understanding the situation assist in detecting and responding to HTs to CM operations. There is evidence that information exchange and collaboration are important elements in the fight against hybrid influence and war. Combating misinformation through public education campaigns can support both the civilian and military elements of CM operations. Specific training can be designed to counter aggressive propaganda and disinformation efforts against personnel in CM operations. This maintains one’s initiative and trust in the aims of the mission.